Associations of the miRNA-146a rs2910164 and the miRNA-499a rs3746444 Polymorphisms With Plasma Lipid Levels: A Meta-Analysis - Liu, Fuqiang; Wang, Shengping; Luo, Zhi (Frontiers in Genetics, 2021)
Background: The studies of miRNAs are vibrant and remain at the forefront in cardiovascular system. Emerging evidences indicate that the genetic polymorphisms of miRNAs gene may affect lipid metabolism, this study aims to clarify the specific correlations between the rs2910164 and rs3746444 polymorphisms and lipid levels. Methods and Results: A comprehensive search of literature was performed from December 31, 2020 to May 31, 2021 by searching of PubMed and the Cochrane database. The standardized mean difference (SMD) and 95% confidence interval (CI) were used to evaluate the differences in lipid levels between the genotypes. rs2910164, a functional polymorphism in the miRNA-146a gene, was associated with increased triglycerides (TG) (SMD = 0.35, 95% CI = 0.15-0.54, P < 0.001), total cholesterol (TC) (SMD = 0.43, 95% CI = 0.16-0.70, P < 0.001) and low-density lipoprotein cholesterol (LDL-C) (SMD = 0.37, 95% CI = 0.11-0.63, P = 0.01) as well as decreased high-density lipoprotein cholesterol (HDL-C) (SMD = -0.27, 95% CI = -0.47--0.07, P = 0.01) levels. rs3746444, a functional polymorphism in the miRNA-499a gene, was only correlated with decreased TG (SMD = -0.09, 95% CI = -0.17--0.01, P = 0.03) levels. Conclusions: The miRNA-146a rs2910164 polymorphism is significantly associated with atherogenic dyslipidemia.